How Do Specific Social Supports (Family, Friend, and Specialist) Reduce Stress in Patients With Substance Use Disorders: A Multiple Mediation Analysis - Yang, Chunyu; Xia, Mengfan; Li, Tianshu; Zhou, You (Frontiers in Psychiatry, 2021)
Perceived social support has been found to reduce the stress of individuals who suffer from substance use disorders. However, the mediating effects of resilience and affect balance in the relationships between specific social supports (family, friend, and significant others) and perceived stress are still unclear. This study focused on substance use disorders (SUD) patients, exploring the mediating roles of resilience and affect balance on the relationships between three dimensions of social supports (family, friend, and specialist) and stress. 339 participants completed questionnaires of perceived social support, resilience, affect balance, and stress. After controlling resilience and affect balance, the results suggested the effects of perceived family and specialist supports on perceived stress were fully mediated, and the association between perceived friend support and perceived stress is partially mediated. The multiple mediation analysis showed resilience is significant in mediating the relationship between specific perceived supports in all models, while affect balance is only significant in mediating the relationship between specialist support and perceived stress. Implications for enriching current theoretical research and strategies for government and practitioners were also discussed.